Triggering Receptor Expressed on Myeloid Cells-1 Agonist Regulates Intestinal Inflammation via Cd177+ Neutrophils - Seo, Dong Hyuk; Che, Xiumei; Kim, Soochan; Kim, Da Hye; Ma, Hyun Woo; Kim, Jae Hyeon; Kim, Tae Il; Kim, Won Ho; Kim, Seung Won; Cheon, Jae Hee (Frontiers in Immunology, 2021)
Triggering receptor expressed on myeloid cell-1 (TREM-1) signaling is expressed on neutrophils and monocytes that is necessary for the successful antimicrobial response and resolution of inflammation in the gut. In this study, we determined the effect of an anti-TREM-1 agonistic antibody (α-TREM-1) on colitis and identify its underlying mechanism of action. Administration of α-TREM-1 alleviated colitis in mice and resolved dysbiosis, which required TLR4/Myd88 signaling. α-TREM-1 increased the production of neutrophil extracellular traps and interleukin-22 by CD177+ neutrophils, which led to pathogen clearance and protection of the intestinal barrier. TREM-1 activation using an α-TREM-1 antibody protects against colitis by rebalancing the microbiota and protecting the epithelium against the immune response as well as modulates the function of neutrophils and macrophages. These results highlight the importance of the TREM-1 pathway in intestinal homeostasis and suggest that α-TREM-1 treatment may be an effective therapeutic strategy for inflammatory bowel disease.